Study of Characteristics of Eggshell Waste Composite by Using Cold Compaction Method - Abu Bakar, Nurul Najwa; Mohamad, Zaleha (Journal of Advanced Mechanical Engineering Applications, 2022)
Eggshell is a new engineering reinforcement retaining excellent properties such as low density, renewable, eco-friendly, and high thermal stability. The research aims to study the characteristics of eggshell waste composite by using the cold compaction method. This research investigates the potential of eggshell waste to be used as water filters. Eggshell waste was mixed with kaolin clay and wheat flour as a binder by using different compositions, physical and microstructure tests were conducted. The result shows that the eggshell has a low-density value. This study also showed that eggshells are suitable as a water filter because microstructural tests show that the sample has pores for water flow.